2018
DOI: 10.1177/0898264318802047
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Screening Mammograms in the Medicare Population Before and After the Affordable Care Act Implementation

Abstract: Objective: This study examined screening mammograms in women aged 65 to 74 years and 75+ years before and after the Affordable Care Act (ACA) implementation. Method: This repeated cross-sectional study of community-dwelling women age 65+ years without a history of breast cancer or mastectomy utilized the Medicare Current Beneficiary Survey and Medicare fee-for-service claims data from 2001 to 2013. We used covariate-adjusted logistic regression with generalized estimating equations, stratified by age group. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…While Bozzi et al (2020) found that the proportion of annual screening mammograms increased for Medicare beneficiaries between 2001 and 2007, prior to cost-sharing elimination, the prevalence of annual screening mammograms among women ages 65 to 74 years began to decline after 2007 and did not increase after the ACA mandate. For women aged 65 to 74 years, the adjusted odds of annual screening mammograms post-ACA was 25% lower than the odds of screening mammograms pre-ACA (Bozzi et al, 2020). In their interrupted time series analyses of utilization trends, Carlos et al (2019) reported that annual screening utilization rose from 36.0% in 2004 to a peak of 42.2% in 2009 among their commercially insured population, before experiencing a steady rate of decline after 2010, eventually reaching 39.9% in 2014.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…While Bozzi et al (2020) found that the proportion of annual screening mammograms increased for Medicare beneficiaries between 2001 and 2007, prior to cost-sharing elimination, the prevalence of annual screening mammograms among women ages 65 to 74 years began to decline after 2007 and did not increase after the ACA mandate. For women aged 65 to 74 years, the adjusted odds of annual screening mammograms post-ACA was 25% lower than the odds of screening mammograms pre-ACA (Bozzi et al, 2020). In their interrupted time series analyses of utilization trends, Carlos et al (2019) reported that annual screening utilization rose from 36.0% in 2004 to a peak of 42.2% in 2009 among their commercially insured population, before experiencing a steady rate of decline after 2010, eventually reaching 39.9% in 2014.…”
Section: Resultsmentioning
confidence: 98%
“…All three studies drew connections between changes in USPSTF guidelines in 2009, which modified screening mammography recommendations to biennial instead of annual for women aged 50 to 74 years and no longer recommended screening mammography among women older than 74 years, and their observed decreases. Bozzi et al and Carlos et al noted that the reductions in screening mammograms occurred indiscriminately of beneficiary age and could have been due changes to physician specialty guidelines instead of changes to USPSTF guidelines (Bozzi et al, 2020; Carlos et al, 2019; Jiang et al, 2015). Carlos et al additionally suggested that few plans required cost-sharing for mammography before the ACA, and those plans that did require cost-sharing only charged patients a small amount.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the fifth leading cause of cancer mortality worldwide, with 685,000 deaths [ 1 ]. Breast cancer diagnosis is more frequent in developed countries [ 2 ]. Controlling and preventing breast cancer is an important priority for health policy makers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%